2017
DOI: 10.1098/rstb.2016.0073
|View full text |Cite
|
Sign up to set email alerts
|

Processing of single-photon responses in the mammalian On and Off retinal pathways at the sensitivity limit of vision

Abstract: Visually guided behaviour at its sensitivity limit relies on single-photon responses originating in a small number of rod photoreceptors. For decades, researchers have debated the neural mechanisms and noise sources that underlie this striking sensitivity. To address this question, we need to understand the constraints arising from the retinal output signals provided by distinct retinal ganglion cell types. It has recently been shown in the primate retina that On and Off parasol ganglion cells, the cell types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 75 publications
4
22
0
Order By: Relevance
“…Rod photoreceptors contribute to vision across a million-fold range of light intensities. At the low end of this range - for example in starlight - photons are few and far between, and retinal circuits face the considerable challenge of detecting and reliably transmitting signals resulting from the absorption of individual photons (reviewed by ( Field et al, 2005 ; Takeshita et al, 2017 )). Other challenges emerge as light levels increase.…”
Section: Introductionmentioning
confidence: 99%
“…Rod photoreceptors contribute to vision across a million-fold range of light intensities. At the low end of this range - for example in starlight - photons are few and far between, and retinal circuits face the considerable challenge of detecting and reliably transmitting signals resulting from the absorption of individual photons (reviewed by ( Field et al, 2005 ; Takeshita et al, 2017 )). Other challenges emerge as light levels increase.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the thresholds of the s-DSGCs approached the lowest thresholds observed among any of the recorded RGCs over the MEA (Fig 1A, gray). These were RGCs with sustained ON responses and large spatial RFs (data not shown): these RGCs are likely ON sustained alpha-cells because they exhibited large spikes over the MEA, presumably produced by large somata (Ravi et al, 2018;Takeshita et al, 2017;Yu et al, 2017). These observations indicated that s-DSGCs are more sensitive to dim flashes of light than the other ooDSGC types and approach (within ~0.5 log unit) the sensitivity of the most sensitive RGCs in the dark-adapted retina.…”
Section: Resultsmentioning
confidence: 84%
“…We found that s-DSGCs were ~10-fold more sensitive to flashes of light near absolute visual threshold than the other three ooDSGC types. Furthermore, s-DSGC sensitivity was within a factor of three of ON-alpha cell sensitivity, which is likely one of the most sensitive RGC types in the mouse retina ((Takeshita et al, 2017), but see (Pan et al, 2016)). One possibility for why s-DSGCs are more sensitive than other ooDSGCs is that they integrate signals over a larger area.…”
Section: Introductionmentioning
confidence: 92%
“…Penteriani & del Mar Delgado [55] review current knowledge on visual signalling in crepuscular and nocturnal birds and mammals and the visual signals that they may use to communicate with others-another example of a topic within this field where many questions remain unanswered. Takeshita et al [56] then review the mechanistic basis for the segregation of visual information from the same rod photoreceptors into two visual pathways that process increments of light intensity (ON) and the other decrements (OFF). Morshedian & Fain [48] then review the reasons why vertebrates evolved ciliary-type photoreceptors rather than the rstb.royalsocietypublishing.org Phil.…”
Section: A Special Issue Devoted To Vision In Dim Lightmentioning
confidence: 99%